A case‐mix‐adjusted comparison of early oncological outcomes of open and robotic prostatectomy performed by experienced high volume surgeons. (29th January 2013) - Silberstein, Jonathan L.; Su, Daniel; Glickman, Leonard; Kent, Matthew; Keren‐Paz, Gal; Vickers, Andrew J.; Coleman, Jonathan A.; Eastham, James A.; Scardino, Peter T.; Laudone, Vincent P.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Radical prostatectomy provides local‐regional control of prostate cancer and is the most common treatment for prostate cancer in the United States. Over the past decade there has been a shift in the surgical approach used to treat this disease, moving from open retropubic approach to robot‐assisted laparoscopic prostatectomy. While robotic prostatectomy has been demonstrated to result in less blood loss, fewer transfusions and shorter hospital duration, it has never been demonstrated in a meaningful prospective manner to result in improved or even equivalent oncological outcomes. Prior attempts to address this question have been hampered by methodological issues with study design, differences in case mix, or differences in surgical learning curve between surgeons. In this retrospective study we compared the oncological outcomes of open radical prostatectomy and robotic prostatectomy limiting our analysis to expert surgeons in their respective surgical approaches. Importantly, the patient cohort contained a majority of patients with intermediate‐ and high‐risk features and all surgeons attempted to adhere to strict oncological principles, including performing complete pelvic lymph node dissections in almost all of the patients in the study. The results demonstrate that oncological outcomes show no significant difference with respect to surgical approach, even for patients with higher risk features, and that there is more variation between individual surgeons than between surgical approaches. Objective To compare early oncological outcomes of robot assisted laparoscopic prostatectomy (RALP) and open radical prostatectomy (ORP) performed by high volume surgeons in a contemporary cohort. Methods We reviewed patients who underwent radical prostatectomy for prostate cancer by high volume surgeons performing RALP or ORP. Biochemical recurrence (BCR) was defined as PSA ≥ 0.1 ng/mL or PSA ≥ 0.05 ng/mL with receipt of additional therapy. A Cox regression model was used to evaluate the association between surgical approach and BCR using a predictive model (nomogram) based on preoperative stage, grade, volume of disease and PSA. To explore the impact of differences between surgeons, multivariable analyses were repeated using surgeon in place of approach. Results Of 1454 patients included, 961 (66%) underwent ORP and 493 (34%) RALP and there were no important differences in cancer characteristics by group. Overall, 68% of patients met National Comprehensive Cancer Network (NCCN) criteria for intermediate or high risk disease and 9% had lymph node involvement. Positive margin rates were 15% for both open and robotic groups. In a multivariate model adjusting for preoperative risk there was no significant difference in BCR rates for RALP compared with ORP (hazard ratio 0.88; 95% CI 0.56–1.39; P = 0.6). The interaction term between nomogram risk and procedure type was not statistically significant. Using NCCN risk group as the covariate in a Cox model gave similar results (hazard ratio 0.74; 95% CI 0.47–1.17; P = 0.2). The interaction term between NCCN risk and procedure type was also non‐significant. Differences in BCR rates between techniques (4.1% vs 3.3% adjusted risk at 2 years) were smaller than those between surgeons (2.5% to 4.8% adjusted risk at 2 years). Conclusions In this relatively high risk cohort of patients undergoing radical prostatectomy we found no evidence to suggest that ORP resulted in better early oncological outcomes then RALP. Oncological outcome after radical prostatectomy may be driven more by surgeon factors than surgical approach.